Fenomena Tari Cokek di Jakarta - Nurul Rohmawati (PANTUN, 2019)
Cokek dance as one of the Betawi arts has experienced dynamic as other arts. The dynamics lies in the presentation of cokek dance performances and cokek dance role today is more used as a foothold by most choreographer to create a new dance work creations were also relatively preferred Betawi community than its role as entertainment at weddings. Allegedly it happens because now the art of thetaste and values prevailing in society. Qualitative research methods with the Theory of Phenomenology is used to examine the phenomenon. The data obtained were later analyzed using philosophical analysis unit shaped descriptive analysis.Keywords: phenomenology, Cokek dance, Betawi